Evaluating the shear capacity of reinforced concrete beams retrofitted with hybrid FRP composite techniques: experimental and analytical study - Joyklad, Panuwat; Chatveera, Burachat; Sua-Iam, Gritsada; Chaimahawan, Preeda; Suthumma, Chisanuphong; Hussain, Qudeer; Paudel, Satish; Saingam, Panumas (My University, 2026)
This study investigates the shear performance of reinforced concrete (RC) beams strengthened with externally bonded hybrid fiber-reinforced polymer systems. The strengthening materials include mild steel strips, glass chopped strand mat (GCSM) fiber-reinforced polymer (FRP) composites, natural basalt fiber-reinforced polymer (BFRP) composites, and hybrid combinations of GCSM and BFRP. The hybrid systems pair low-strain GCSM composites with higher-strain natural BFRP to improve both strength and ductility. Eleven RC beams were tested and compared to a control specimen that lacked shear reinforcement over half the span. All strengthened beams showed substantial improvements over the unstrengthened control (35.49 kN). Peak loads ranged from 59.94 kN to 144.86 kN, corresponding to increases of approximately 69–308% relative to the control. In term of deflections again peak load, strengthening increased deflections by roughly 4.4–10.5 times versus the control beam. Strip orientation and layering strongly influenced crack redistribution and energy dissipation. The hybrid GCSM–BFRP systems provided a balanced improvement in strength and post-peak behavior.These results indicate that steel-strip and composite-based strengthening approaches offer affordable and effective solutions for retrofitting shear-deficient RC elements, particularly in post-disaster or resource-limited settings.
Keywords: GCSM; Green Infrastructure; Hybrid FRP, Basalt FRP; Natural BFRP; RC beams; Shear strengthening; Sustainable Development